IMPLEMENTASI PENGUASAAN OBYEK GADAI (MOTOR) DI LEMBAGA PEGADAIAN DENPASAR - Hermawan Cavalera, Arick; Surya Dharma Jaya, Ida Bagus; Dedy Priyanto, I Made (Kertha Semaya : Journal Ilmu Hukum; Vol. 02, No. 01, Februari 2014)
The paper titled The Implementation of Object Mastery on Pledge (Motor) in Denpasar Mortgage Institution. In writing this paper is used the empirical juridica method that using thel primary data (field) which is then analyzed or assessed by the legislation, the qualitative analysis is then presented by descriptive analysis. Assurance are the main conditions in mortgage activity. In a pledge that the main principle is the displacement of power over the object to the lien holder, not the right of ownership only this is expressly contained in Article 1150 Civil Code. But mastery pawn object (motor) in Denpasar Mortgage Institutions still found a violation of the principle of fiduciary.
Keywords: Implementation, Fiduciary Object, Mortgage Institutions